Community-Based Exercise Programs dalam Mengurangi Fear of Falling dan Meningkatkan Quality of Life pada Lansia: A Systematic Literature Review - Rafifah, Amirah Hasna, -; Hanif Maulana; Saffanah (UI Scholars Hub, 2026)
The global increase in the elderly population presents significant challenges in maintaining independence and quality of life among older adults. One of the most common problems experienced by the elderly is fear of falling, which negatively affects physical activity, balance, and psychological well-being. Community-based exercise programs represent an approach that not only improves physical function but also strengthens social interaction and self-confidence among older adults. This study aims to review community-based exercise programs in reducing fear of falling and improving quality of life among the elderly through a Systematic Literature Review (SLR) using the PRISMA 2020 guidelines. The literature search was conducted in the PubMed, Scopus, Google Scholar, and Crossref databases with inclusion criteria consisting of Randomized Controlled Trial (RCT), quasi-experimental, and prospective studies published between 2020 and 2025. From a total of 1,288 articles identified, five studies met the final inclusion criteria and were analyzed thematically. The findings indicate that community-based exercise programs, particularly multicomponent exercises such as the Otago Exercise Programme, Fall Prevention Exercise Program, and group-based exercise, significantly reduce levels of fear of falling (p < 0.05) and improve quality of life as measured by instruments including the Falls Efficacy Scale International (FES-I), 12-Item Short Form Health Survey (SF-12), and 36-Item Short Form Health Survey (SF-36). In conclusion, participation of older adults in community-based exercise programs contributes positively to both physical and psychological well-being; therefore, the implementation of community-based exercise should be strengthened through multisectoral collaboration and the involvement of healthcare professionals to support sustainable healthy aging.